Efficacy of Two Rotary Instruments For Gutta Percha Removal During Root Canal Retreatment - Dhillon, JS; Bhagat, A; Chhabra, G (Bangladesh Journal of Dental Research & Education, 2014)
Aim - Evaluate the efficacy of Pro Taper and Pro Taper Retreatment instruments in the removal of gutta-percha during retreatment of straight root canals in comparison with Hedstrom files. Methodology -The root canals of 30 Maxillary central incisors were instrumented by step back procedure and obturated with lateral condensation before the teeth were randomly divided into three groups of 10 specimens each i.e. Group I-using Hfiles, Group 2- using Pro Taper and Group 3- using Pro Taper retreatment. Radiographs were taken after the filling removal and the canal wall cleanliness was evaluated. Roots were divided into apical, middle and coronal parts and scored on a scale of 0 (no debris), 1(25-50% of walls covered with debris and 3 (>50% of walls covered with debris).Number of fractured instruments were also evaluated in each group. Results-There was no significant difference (p>0.05) between the three groups in terms of the debris seen radio graphically after retreatment. Conclusion - All systems evaluated ex vivo were equally effective in removing gutta percha during retreatment. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20250 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 56-60